Influence of Debt to Equity Ratio, Return on Asset Ratio, and Firm Size on Audit Delay - Mutiara Lusiana Annisa; Ruth Samantha Hamzah (Faculty of Economics, Universitas Sriwijaya, 2020)
This study analyses the effect of debt to equity ratio, return on asset ratio, and firm size toward audit delay. The population in this study is listed companies on mining sector at the Indonesia Stock Exchange circa 2017-2019, which consists of 13 companies. This study employed multiple regression analysis and purposive sampling as an analysis method and sampling technique, respectively. The result shows that debt to equity ratio and return on asset ratio do not have a significant effect on audit delay, meanwhile firm size significantly affects audit delay.